Knowledge and Hygiene Practice during Menstruation in the Adolescents (Bangladesh Journal of Obstetrics & Gynaecology, 2025)
Background: Adolescent girl requires specific attention as it marks an important milestone menarchae and hence good hygienic practices during menstruation are crucial to maintain a healthy life. Aims andObjectives: The survey was conducted to assess the knowledge about menstruation and menstrual hygiene.Materials and Method: A cross-sectional study was carried out on the adolescent daughters of Aya of Bangladesh Medical College between the age of 11-19 years who resides in slum and semi slum area. Total 56 adolescent girls were interviewed. The data were collected through mobile and in person interview of the adolescent girls with due consent of their mother. Data was collected using pretested proforma. The questionnaire consisted of sociodemographic details, knowledge about menstruation, practices, hygiene followed during menstruation. All the respondents were assured that their information will be kept confidential. At the end of the interview, the girls were educated about the facts of menstruation and explained about the hygiene during menstruation.Result: Among the 56 adolescent girls, 64% were between 11 and 14 years. About 46.4% mothers were illiterate; 67% girls had menarche at 11-12 years and 71% had history of vaginal discharge. About 60% had no knowledge of menses before menarche. The source of information was mother in 57.1%. About 64.3% girls used sanitary pad and the 14.3% used cloth pieces. About 78.6% use razor for hair shaving. 17.9% reuse cloth. Only 17.9%% change pad 6 hourly, other keep pads for longer period.Conclusion: This study reported that menstrual hygiene was unsatisfactory among adolescent girls. Therefore, girls should be educated about the facts of menstruation and proper hygienic practices.Bangladesh J Obstet Gynaecol, 2025; Vol. 40(1): 19-23